8. Drezdeńska Dywizja Piechoty im. Bartosza Głowackiego na Ziemi Łódzkiej w latach 1946–1949 - Jarno, Witold (Przegląd Nauk Historycznych, 2013)
The article describes the history of the 8th Infantry Division in district of Łódź in the years 1946–1949. It is a little known episode in the history of this province. This division was created in 1944 and took part in the final period of the Second World War. After the war was directed to the fight against the armed underground in south-easterly Poland. In autumn 1946 the Ministry of Defence decided to move the 8th Infantry Division to new garrisons, situated in the Łódź region. Military units were located in Łódź (Command of the 8th Division and 34 Infantry Regiment), Skierniewice (32 Infantry Regiment and 37 Regiment of Artillery, Łowicz (36 Infantry Regiment) and Kutno (19 Sapper Battalion and 11 Antitank Artillery Battalion). Commanders of this Infantry Division were in the years 1946–1949: Colonel Stanisław Habowski, Colonel Józef Bielecki and Colonel Józef Batkiewicz. The article describes organization of the 8th Infantry Division and changes in its structure in the years 1946–1949, higher military cadre, training and changes in units dislocation. History of the 8th Infantry Division in the Łódź region ended in 1949, when it was moved to the Central Pomerania.